Pulmonary leucostasis in a patient with chronic lymphocytic leukaemia. (12th February 2015) - Awad, Christina; Parikh, Rajul; Fardous, Yara
Abstract : A 71-year-old woman with no chronic medical problems presented to the emergency room with a 24-month history of chronic non-productive cough, malaise, increasing fatigue and weight loss. On physical examination, she had significant cervical and axillary lymphadenopathy with no organomegaly. She was diagnosed with chronic lymphocytic leukaemia (CLL) due to her lymphocyte count of 1789.4×10 9 /L on admission. A few days after hospitalisation, she developed respiratory failure requiring intubation. A chest X-ray showed interstitial markings. The abnormally high number of mature lymphocytes could have caused leucostasis in the lungs of this patient with CLL.